Germinations 6 : Europäische Ausstellung junger Künstler. - Peeters, Jacques; Wegmann, Horst; Morin, Martine; Wessel, Barbara; Hegyi, Lorand; Lauf, Cornelia; Ludwig Forum für Internationale Kunst, Aachen; Germinations Aachen 1991 ([S.l.] : Germinations, 1991)
van den Heuvel, Hilde ; Keunen, Hilde ; Baumgartner der Ältere, Franz ; Ebner, Käthe ; Frenzel, Nicole ; Glanz, Katrin ; Herrmann, Jens ; Karch, Michaele ; Linhard, Monica ; Richter, Ute ; Schliesser, Les ; Welsch, Matthias ; Cizmárik, Marián ; Kubinský, Bohus ; Písarik, Petr ; Rádová, Elen ; Andersen, Martin Erik ; et al.
Ludwig Forum für internationale Kunst, Aachen, Aix-la-Chapelle, 28.11.1991-02.02.1992
kunstcatalogus